Successful fishing for nucleus pulposus progenitor cells of the intervertebral disc across species. Issue 2 (27th June 2018) - Sakai, Daisuke; Schol, Jordy; Bach, Frances C.; Tekari, Adel; Sagawa, Nobuho; Nakamura, Yoshihiko; Chan, Samantha C.W.; Nakai, Tomoko; Creemers, Laura B.; Frauchiger, Daniela A.; May, Rahel D.; Grad, Sibylle; et al.
Abstract : Background: Recently, Tie2/TEK receptor tyrosine kinase (Tie2 or syn. angiopoietin‐1 receptor) positive nucleus pulposus progenitor cells were detected in human, cattle, and mouse. These cells show remarkable multilineage differentiation capacity and direct correlation with intervertebral disc (IVD) degeneration and are therefore an interesting target for regenerative strategies. Nevertheless, there remains controversy over the presence and function of these Tie2 + nucleus pulposus cells (NPCs), in part due to the difficulty of identification and isolation. Purpose: Here, we present a comprehensive protocol for sorting of Tie2 + NPCs from human, canine, bovine, and murine IVD tissue. We describe enhanced conditions for expansion and an optimized fluorescence‐activated cell sorting‐based methodology to sort and analyze Tie2 + NPCs. Methods: We present flow cytometry protocols to isolate the Tie2 + cell population for the aforementioned species. Moreover, we describe crucial pitfalls to prevent loss of Tie2 + NPCs from the IVD cell population during the isolation process. A cross‐species phylogenetic analysis of Tie2 across species is presented. Results: Our protocols are efficient towards labeling and isolation of Tie2 + NPCs. The total flow cytometry procedure requires approximately 9 hours, cell isolation 4 to 16 hours, cell expansion can take up to multiple weeks, dependent on the application, age, disease state, and species. Phylogenetic analysis of the TEK gene revealed a strong homology among species. Conclusions: Current identification of Tie2 + cells could be confirmed in bovine, canine, mouse, and human specimens. The presented flow cytometry protocol can successfully sort these multipotent cells. The biological function of isolated cells based on Tie2 + expression needs to be confirmed by functional assays such as in vitro differentiation. in vitro culture conditions to maintain and their possible proliferation of the Tie2 + fraction is the subject of future research. Abstract : Colony forming units from assessed species. Nucleus pulposus progenitor cells from different species sorted on Tie2 expression were cultured in semi‐solid methylcellulose medium. Fibroblastic colony forming units (CFU‐F) and spherical colony forming units (CFU‐S) emanate as two distinguishable colony types. Scale bar represents 50 μm.